2011
DOI: 10.1002/csr.260
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Reputation: A Combination of Social Responsibility and Industry

Abstract: We use the technique of panel data in a sample of 320 American listed companies from 2003 to 2007 to estimate a model of corporate reputation, measured by the Fortune index. We propose that corporate social responsibility (CSR) is a key driver of corporate reputation given its potential to foster hard-to-duplicate competitive advantage. Our model embodies the multidimensional concept of CSR, presenting a five dimensional construct -employee relations, diversity issues, product issues, community relations, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
336
5
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(400 citation statements)
references
References 99 publications
(336 reference statements)
32
336
5
8
Order By: Relevance
“…Many researchers have investigated CSR from the perspective of particular sectors or industries (e.g., Wagner et al 2002;Cuganesan et al 2010) and studying industry effects is a widely adopted practice in CSR research (e.g., Young and Marais 2012;Melo and Garrido-Morgado 2011). Specifically, varying industry levels of stakeholder activism and stakeholder interest in CSR appear to influence the relationship between firms' CSR and financial performance (Chand and Fraser 2006).…”
Section: Industry Effectsmentioning
confidence: 99%
“…Many researchers have investigated CSR from the perspective of particular sectors or industries (e.g., Wagner et al 2002;Cuganesan et al 2010) and studying industry effects is a widely adopted practice in CSR research (e.g., Young and Marais 2012;Melo and Garrido-Morgado 2011). Specifically, varying industry levels of stakeholder activism and stakeholder interest in CSR appear to influence the relationship between firms' CSR and financial performance (Chand and Fraser 2006).…”
Section: Industry Effectsmentioning
confidence: 99%
“…One of the advantages of engaging in CSR is that it can improve the firm's reputation (Gardberg and Fombrun, 2006;Heikkurinen, 2010;Babiak and Trendafilova, 2011;Melo & Garrido-Morgado, 2012;Lin et al, 2016). Enhanced stakeholder perceptions are a valuable resource that will lead to improved financial performance (Walker and Mercado, 2015).…”
Section: Orporate Social Responsibility (Csr) Consultancies Increasmentioning
confidence: 99%
“…Corporate reputation is an important factor in stakeholders' decisions, for employees deciding to work for a company, for investors to invest in it, and for consumers to buy its product and services [71]. A number of studies (e.g., Bhattacharya and Sen 2004 [72]; Du et al, 2010 [73]; Melo and Garrido-Morgado 2012 [74]) have shown that companies benefit from engaging in responsible corporate activities [75]. Companies profit from obtaining favourable consumer awareness, attitude and a sense of attachment as well as by building a long lasting positive corporate image and good reputation [75].…”
Section: Corporate Reputation and Critical Consumerismmentioning
confidence: 99%